2020
DOI: 10.2147/dmso.s282403
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Serum Uric Acid, Urea Nitrogen, and Urine Specific Gravity Levels at 16–18 Weeks of Gestation with the Risk of Gestational Diabetes Mellitus</p>

Abstract: To evaluate the associations of serum uric acid (UA), urea nitrogen (UN), and urine specific gravity (USG) levels in the first trimester of pregnancy with the risk of gestational diabetes mellitus (GDM). Patients and Methods: A retrospective cohort study was conducted in 1,769 pregnant women aged 31.55 ± 3.91 years. UA, UN, and USG levels were measured during the 16-18th week of gestation. GDM was diagnosed by an oral 75 g glucose tolerance test during the 24-28th week of gestation. Results: A multivariate adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Rehman et al 24 reported in their study of 172 pregnant women in the first trimester of pregnancy where mean uric acid levels of GDM mothers were higher compared to the control group; 3.73mg/dL (221.9µmol/ L) vs. 3.19mg/dL (189.74µmol/L). Li et al 25, in their study of 1769 pregnant women, also reported that GDM group mothers had higher mean serum uric acid levels than non-GDM mothers (216.45µmol/L vs. 209.36µmol/ L). They concluded that higher uric acid levels and a higher composite kidney function biomarker score during the 16-18th week of gestation were positively and independently associated with an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 94%
“…Rehman et al 24 reported in their study of 172 pregnant women in the first trimester of pregnancy where mean uric acid levels of GDM mothers were higher compared to the control group; 3.73mg/dL (221.9µmol/ L) vs. 3.19mg/dL (189.74µmol/L). Li et al 25, in their study of 1769 pregnant women, also reported that GDM group mothers had higher mean serum uric acid levels than non-GDM mothers (216.45µmol/L vs. 209.36µmol/ L). They concluded that higher uric acid levels and a higher composite kidney function biomarker score during the 16-18th week of gestation were positively and independently associated with an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, 19 studies were excluded after the full-text screening. Finally, 23 studies were eligible for inclusion in the present study [18][19][20][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Table 1 summarizes the characteristics of the included studies.…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%
“…The maternal blood uric acid concentration during pregnancy was measured in 21 of 23 studies at or before the 20th week of gestation [18][19][20]25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] , and the remaining studies measured it after the 20th week of gestation 26,44 . The maternal blood uric acid concentration during pregnancy was measured using calorimetric assays 18,20,25,27,28,[30][31][32][33][36][37][38][39]41 or a spectrometric method 29 , whereas eight out of 23 included studies did not provide data regarding the method of maternal blood uric acid measurement 19,26,34,35,40,[42][43][44] . Among the 23 included studies, five studies collected blood samples after 8-12 h of fasting for the measurement of maternal uric acid…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research has examined UA levels in blood during pregnancy as a potential indicator of increased risk of gestational diabetes, hypertension, preeclampsia, and other related adverse health outcomes. Serum UA levels, particularly in early pregnancy, have been associated with increased risk of developing GDM (8)(9)(10)(11). High concentrations of serum UA during pregnancy have also been associated with high BP and preeclampsia, as well as related poor birth outcomes such as lower birth weight and earlier gestational age at birth (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%